Upaya Pencegahan Penularan Covid-19 pada Anak Usia Dini Melalui Media Video Edukasi - Diana, Ari; Hajiriah, Titi Laily; Harisanti, Baiq Muli; Fitriani, Herdiyana; Samsuri, Taufik (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Health protocols were quickly implemented to break the chain of spread of Covid-19, such as: health campaigns, the use of protective attributes, and distance learning which suddenly had to be implemented in every school. The widespread spread of Covid-19 in Indonesia has an impact on all children in Indonesia. This has resulted in many educational forums being overwhelmed in providing supervision, as well as providing optimal learning materials, especially providing knowledge to early childhood about the dangers of a pandemic and the importance of maintaining personal hygiene to prevent the transmission of Covid-19, which is considered relatively difficult, because there is no direct relationship. direct. Through this community service activity, the introduction of the prevention of Covid-19 transmission is carried out through the distribution of online educational videos, in order to provide knowledge and increase the sensitivity of early childhood to be able to maintain personal hygiene and be aware of the dangers that lurk, so that early childhood can consciously do the habit of washing hands, wearing masks, and keeping a distance in daily life to prevent the spread of Covid-19 that hit.